Karakteristik Histopatologik dan Imunofenotipik Kanker Payudara di Rumah Sakit Cipto Mangunkusumo Jakarta, Indonesia - Primariadewi Rustamadji; Stephanie Marisca (Medicinus, 2018)
Introduction: Breast cancer can be classified into luminal A, luminal B, Her2+, dan basal-like molecular subtype according to genetic profile and immunophenotype. The aim of this study is to assess histopathologic and immunophenotype characteristics of breast cancer in Cipto Mangunkusumo Hospital Jakarta, Indonesia.Material and methods: This study is a cross-sectional retrospective study. The sample was 2632 breast cancer case in Department of Anatomical Pathology Cipto Mangunkusumo Hospital from the year 2011 until 2015. ER, PR, Her2, Top2 α, and Ki67 immunohistochemical stain was then grouped into luminal A (ER+/PR+/Her2-/Ki67<20%) subtype, luminal B (ER+/PR+/Her2-/Ki67≥20%) subtype, Her2+ (ER-/PR-/Her2+) subtype, and basal-like (ER-/PR-/Her2-) subtype. Kendall’s Tau analysis was done to assess association between sample characteristics and molecular subtype, association between top2α positive and molecular subtype.Result: The most prevalent to the less prevalent breast cancer molecular subtype was luminal B (43,9%), Her2+ (14,6%), luminal A (14,0%), and basal-like (11,3%). There was a significant association between the tumor stage and breast cancer subtype (p=0,0001). There is also a significant association between Top2α expression and molecular subtype (p=0,0001).Conclusion: The most prevalent breast cancer molecular subtype was luminal B. There was an association between breast cancer molecular subtype and a higher degree and Top2α expression.